2018
DOI: 10.15407/ujpe63.11.1036
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibrium, Thermodynamic Limit, and Melting Temperature in Nanocrystals

Abstract: The phase equilibrium condition is shown to be strictly satisfied only in the thermodynamic limit. The notion of melting temperature in the thermodynamic limit is introduced. Formulas are obtained that determine the melting conditions and the melting temperature for finite systems including nanocrystals. The validity of those formulas is confirmed, by comparing them with experimental data for organic materials in porous solids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…By comparing this value with the difference between the surface tension coefficients at the rotational phase-matrix and melt-matrix interfaces, which is equal to [12] ( ∞ ) − ( ∞ ) = −4.7 × 10 −3 N/m, we see that the difference in the latter case is much larger. Let us determine the specific heat of the solidphase transition for 1-octadecene in various porous silica gel matrices.…”
Section: Discussion Of Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…By comparing this value with the difference between the surface tension coefficients at the rotational phase-matrix and melt-matrix interfaces, which is equal to [12] ( ∞ ) − ( ∞ ) = −4.7 × 10 −3 N/m, we see that the difference in the latter case is much larger. Let us determine the specific heat of the solidphase transition for 1-octadecene in various porous silica gel matrices.…”
Section: Discussion Of Resultsmentioning
confidence: 95%
“…By studying the infrared spectra of 1-octadecene in pores of porous silica gel, the temperatures of the solid-state phase transition, Orot , are determined. In our previous works [12,17], it was shown that it is expedient to describe the open-porous systems, with porous silica gels belonging to them, by the ratio / between the silica gel surface area and the silica gel pore volume rather than by the pore radius. Therefore, the dependences of the solid-phase transition temperature Orot on this ratio are plotted for bulk 1-octadecene and 1-octadecene in various silica gel matrices (Fig.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the conditions of reality of Russian industrial enterprises to supply spare parts (including ones of foreign manufacture) is difficult and to predict when the break occurs is not always possible. Therefore, with a slight breakdown, the entire production line can stop (Zhang and Chang, 2011;Yumashev et al, 2019;Bulavin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%